Efficacy of Dexamethasone-Enhanced Transversus Abdominis Plane Block for PostoperativePain Management in Pediatric Laparoscopic Surgeries: A Prospective Randomized Trial - Saraswathi Nagappa; Ajith Annadurai; Chandrakala . (RGUHS Journal of Medical Sciences)
Background amp Objectives Pediatric pain management is often inadequate due to unique challenges and treatment limitations. This study evaluates the effectiveness of ultrasound-guided transversus abdominis plane TAP block with 0.2 Ropivacaine alone versus TAP block with 0.2 Ropivacaine and Dexamethasone as an adjuvant in pediatric patients undergoing elective laparoscopic abdominal surgery.Methods A total of 90 pediatric patients aged between 8-16 years belonging to ASA I and II scheduled for elective laparoscopic abdominal surgeries under general anesthesia were selected. Participants were divided into Group 1 TAP block was performed under USG guidance with 0.5 mlkg 0.2 Ropivacaine. Group 2 TAP block with 0.5 mlkg 0.2 Ropivacaine with Dexamethasone 0.3 mgkg. A standard anesthesia technique was followed. After surgery patients were observed in the post-anesthesia care unit. Quality of analgesia was assessed using the CHEOPS score Childrenrsquos Hospital Eastern Ontario Pain Scale in the immediate postoperative period and then at regular intervals postoperatively.Results The mean age of the study participants was 5.81 plusmn 1.96 years with a male preponderance 67. The primary outcome the first time to rescue analgesia was prolonged in the dexamethasone group P 0.000. CHEOPS score was statistically significant at 4 and 6 hours with a P-value of 0.01 and 0.00 respectively.Conclusion Our study concludes that ultrasound-guided transverse abdominis plane block with 0.2 Ropivacaine with dexamethasone as an adjuvant is a good alternative for postoperative analgesia compared to TAP block with 0.2 Ropivacaine alone